PkM Optimalisasi Mekanisme Koping Masyarakat Menghadapi Pandemi Yang Berkepanjangan: Indonesia - Nurul Laili; Nove Lestari; Vela Purnamasari; Wahyu Tanoto (STIKES dan AKZI Karya Husada Kediri, 2022)
A prolonged pandemic with various policies in all sectors of life has an impact on the physical and psychic of individuals. People feel a continuous increase in stress and decreased physical condition. The problems of life due to a prolonged pandemic require a person to be able to adapt to conditions, which can affect individual coping mechanisms. The purpose of community service activities is to provide education about ways of adaptive coping mechanisms in dealing with prolonged pandemic conditions so that people are more able to think positively and be able to adapt and find constructive solutions for their next life. Education or counseling will be held from March 31, 2022, to April 2, 2022, in the PKM Puhjarak Working Area, Kediri Regency, East Java. 20 participants attended. The number of students who participated in the activity was 3 students. The method used is lecture, discussion/question and answer using leaflet media, and explanation of material using LCD and laptop media. From the results of interviews and filling out questionnaires on how to cope with community coping mechanisms during a prolonged pandemic, it was found that most of the respondents had adaptive coping mechanisms and almost half of the respondents had maladaptive coping mechanisms. Adaptive coping mechanisms during a prolonged pandemic can be done by improving problem-solving strategies by learning and trying to adapt to new situations, accepting conditions and staying positive about situations, asking for help from others and seeking information, and making plans to solve problems and straighten thoughts or perceptions of the problem.